Ovicidal activity of Pithecellobium dulce (Family: Fabaceae) leaf and seed extracts against fi lariasis vector mosquito Culex quinquefasciatus (Diptera: Culicidae) - Mohan Rajeswary, S. L. Hoti, Giovanni Benelli, Marimuthu Govindarajan (Journal of Medicinal Herbs and Ethnomedicine, 2015)
Mosquito-borne diseases with an economic impact create a loss in commercial and labor outputs, particularly in countries with tropical and subtropical climates. Mosquito control is facing a threat because of the emergence of resistance to synthetic insecticides. Insecticides of botanical origin may serve as suitable alternative biocontrol techniques in the future. In view of recently increased interest in developing plant origin insecticides as an alternative to chemical insecticide, in the present study ovicidal efficacy of different solvent leaf and seed extract of Pithecellobium dulce against filariasis vector C. quinquefasciatus. The ovicidal efficacy of the crude leaf extracts of P. dulce with five different solvents, such as benzene, hexane, ethyl acetate, methanol, and chloroform, was tested against C. quinquefasciatus. Ovicidal activity was determined against C. quinquefasciatus mosquito to various concentrations ranging from 100 to 600 mg/L under the laboratory conditions. Among five solvent tested the maximum efficacy was observed in the leaf and seed methanol crude extract was found to be most effective for ovicidal activity against vector mosquito. The extract of methanol exerted 100% mortality at 500-600 mg/L against C. quinquefasciatus. From the result, it can be concluded the crude extract of P. dulce was a potential candidate to develop newer and safer ovicides against C. quinquefasciatus.